Nanotechnology Knowledge and Attitude among Undergraduate Dental Iraqi Students - Zainab Mahmood Al-Jammali; Anas Moez Al-Yasiry; Azad Mohamed AlMuthaffer (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Nanotechnology is “a term that involve a spectrum of technologies, techniques and processesthat can deal with a matter at the nanoscale”. Many new diagnostic modalities and nano-delivery systemsthat have been introduced by improvement of the materials mechanical and physical properties’ in the fieldof dentistry.The aim of study was to evaluate undergraduate dental student perceptions of nanotechnologyin Iraq. Method: This study was based on an online questionnaires distributed to students of dentistry forthe five stages, a number of students (417), the questioner include general information and then questionsdistributed into four axes. The generation of a single variable in the second, and third axes was analyzedby five point of Likert scale. Result: 58% of students had an idea about nanotechnology, while 42% ofstudents did not had an idea about nanotechnology. the largest percentage of students have difficulties inaccessing information about nanotechnology. The largest percentage of the student want to introduce thenanotechnology in the curriculum, also largest percentage of the student wish to search information aboutthe nanotechnology and support the use of nanotechnology in clinic. Conclusion: Based on the results ofthis study, the dental students of University of Babylon have inadequate knowledge about nanotechnologyand its applications in field of Dentistry. We think that the incorporation of nanotechnology in the dentistrycurriculum of colleges in Iraq was mandatory.